Incidence of epilepsy among patients with cerebral palsy (CP) in Yayasan Pemeliharaan Anak Cacat (YPAC) â Medan (Faculty of Medicine Universitas Indonesia, 2002)
Epilepsy is a chronic condition due to cerebral function disorders. Epilepsy occurs as a common complication of many neurological disorders such as cerebral palsy (CP) that can cause further brain damage if especially they are accompanied with prolonged seizure. The incidence of epilepsy among patients with CP varies, 25-35%. The high incidence of epilepsy among patients with CP suggests that these disorders has common or related origins. We carried out a retrospective study to determine the incidence of epilepsy among patients with CP registered July 1988 to June 1998 in YPAC Medan and to determine whether the incidence of epilepsy was different according to type of CP. Data was compiled from medical records, including name, sex, parity, mothers age, prenatal, perinatal, and postnatal history, and EEG resuts. Data were analysed using statistical computer program and its significance was evaluated by chi square test at p < 0.05. There were 67 cases with CP, 53 cases spastic CP, 13 cases mixed CP and one case dyskinetic CP. Of the 67 cases CP, 47.8% were male, 52.2% female with the mean age of 50.3 (SD 36.9) months. There were 25 (37.3%) patients CP associated with epilepsy, 72% general seizures, 20% partial seizures, and 8% infantile spasm. The incidence of epilepsy was significantly different among patients with CP associated with the type of CP and gestational age, p < 0.05. We concluded that the incidence of epilepsy among patient with CP in YPAC Medan was 37.3% and showed significant difference in CP according to type and gestational age. (Med J Indones 2002; 11: 158-63) Keywords: epilepsy, cerebral palsy, obstetric history, gestational age